Menguak Kebenaran Ilahi: Integrasi Filsafat, Sejarah, dan Biologi dalam Perspektif Iman Kristen - Tenni Anton Toy; Ekhat Binti Patangun (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper aims to explore and integrate three disciplines—philosophy, history, and biology—in order to strengthen and clarify the rational foundation of the Christian faith. Using a qualitative approach, the author examines the contributions of philosophy in formulating rational arguments for the existence of God, the historical connections in the development of the early church, and the accuracy of biblical narratives based on archaeological findings. Biology, particularly through the complex structure of DNA and the order found in living systems, is also viewed as evidence of a divine design underlying all of creation. Through the synthesis of these three disciplines, this article asserts that the Christian faith is not in conflict with reason and science but can be defended logically and scientifically. Thinkers such as Plantinga and Craig demonstrate how philosophical arguments and historical data support the validity of faith, while scientists like Francis Collins show how science can deepen our understanding of God's greatness. This integration is intended as a constructive response to the challenges of modernity and as a foundation for Christians to maintain a firm, intelligent, and relevant faith in the midst of changing times.